Measuring financial asset return and volatility spillovers, with application to global equity markets - Francis X. Diebold; Kamil Yilmaz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2007)
We provide a simple and intuitive measure of interdependence of asset returns and/or volatilities. In particular, we formulate and examine precise and separate measures of return spillovers and volatility spillovers. Our framework facilitates study of both non-crisis and crisis episodes, including trends and bursts in spillovers, and both turn out to be empirically important. In particular, in an analysis of sixteen global equity markets from the early 1990s to the present, we find striking evidence of divergent behavior in the dynamics of return spillovers vs. volatility spillovers: Return spillovers display a gently increasing trend but no bursts, whereas volatility spillovers display no trend but clear bursts.
urn:nbn:de:hebis:30-38118
Keywords: F30; G15; F36; 330; Asset Market; Asset Return; Stock Market; Emerging Market; Market Linkage; Financial Crisis; Herd Behavior; Contagion; Kapitalertrag; Finanzmarkt; Volatilität; Spillover-Effekt; Finanzmarktkrise; Internationaler Finanzmarkt; Aktienmarkt; Welt